The librarian's nitty-gritty guide to social media - Solomon, Laura, 1967- (ALA Editions, an imprint of the American Library Association, 2013)
Social media doesn't just "happen"; it is easy to learn but can take a long time to master. Learn how to use social media more effectively, discover its pitfalls, and examine how a well developed social media network can be mobilized in times of crisis, financial or otherwise.